Development of free neuromasts with special reference to sensory polarity in larvae of the willow shiner, Gnathopogon elongatus caerulescens (teleostei, cyprinidae) - Mukai, Yukinori; Kobayashi, Hiroshi (Zoological Society of Japan, 1995)
To find how larval fish sense mechanical stimuli via their free neuromasts, we examined morphological changes in free neuromasts in the larval willow shiner, Gnathopogon elongatus caerulescens. Free neuromasts were found on the body surface of newly hatched larvae and their number increased on both the head and trunk with larval growth. The apical surface of free neuromasts changed in outline from a circle to a lozenge shape as the number of sensory cells increased in the prelarval stage, and then the cupulae of the free neuromasts changed from a stick-like to a blade-like shape. Seven-day-old larvae were at the postlarval stage and had many free neuromasts that were nearly mature. All free neuromasts contained sensory cells of opposing polarity. The orientation of the maximum sensitivity of free neuromasts, decided from the polarity of the sensory cells, coincided with the minor axis of the lozenge-shaped outline of the apical surface of the free neuromasts, and was in the same axis as the direction in which the blade-like cupulae bent. The change to a blade-like shape would cause a stimulus parallel to the minor axis to be perceived as being stronger than the same stimulus from other directions. The polarity of trunk neuromasts was usually oriented along the antero-posterior axis of the fish body, but a few had dorso-ventral orientation. On the head, free neuromasts were oriented on lines tangential to concentric circles around the eye.